2007
DOI: 10.1029/2006je002856
|View full text |Cite
|
Sign up to set email alerts
|

Vertical dust mixing and the interannual variations in the Mars thermosphere

Abstract: [1] Mars winter polar warming is a phenomenon of the lower thermosphere temperatures and densities that is well documented by in situ accelerometer data taken during spacecraft aerobraking maneuvers. Previous work by Bougher et al. (2006) simulates two specific time periods, corresponding to existing aerobraking data sets, and confirms the existence of winter polar warming structures in the Martian upper atmosphere, using the coupled Mars General Circulation Model-Mars Thermosphere General Circulation Model (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(122 citation statements)
references
References 33 publications
10
111
1
Order By: Relevance
“…Figure 13 illustrates coupled MGCM-MTGCM simulations for Ls = 90 (aphelion) and 270 (perihelion) conditions, demonstrating that the basic features of the Martian thermospheric winter polar warming are controlled by seasonal changes in the solar plus tidal forcing, the corresponding variations in the strength of the inter-hemispheric Hadley circulation, and the resulting changes in the magnitude of the adiabatic heating near the winter poles. Calculations of polar warming show that perihelion adiabatic heating can be highly variable from one Mars year to the next, and more than twice as strong as that for aphelion conditions (Bougher et al 2006b;Bell et al 2007). Finally, without the deep inter-hemispheric Hadley circulation made possible using these coupled lower and upper atmosphere simulations, winter polar warming features in the Mars thermosphere would not be reproduced at all (Bell et al 2007).…”
Section: Ncar Coupled Mgcm-mtgcm (Mars)mentioning
confidence: 98%
See 2 more Smart Citations
“…Figure 13 illustrates coupled MGCM-MTGCM simulations for Ls = 90 (aphelion) and 270 (perihelion) conditions, demonstrating that the basic features of the Martian thermospheric winter polar warming are controlled by seasonal changes in the solar plus tidal forcing, the corresponding variations in the strength of the inter-hemispheric Hadley circulation, and the resulting changes in the magnitude of the adiabatic heating near the winter poles. Calculations of polar warming show that perihelion adiabatic heating can be highly variable from one Mars year to the next, and more than twice as strong as that for aphelion conditions (Bougher et al 2006b;Bell et al 2007). Finally, without the deep inter-hemispheric Hadley circulation made possible using these coupled lower and upper atmosphere simulations, winter polar warming features in the Mars thermosphere would not be reproduced at all (Bell et al 2007).…”
Section: Ncar Coupled Mgcm-mtgcm (Mars)mentioning
confidence: 98%
“…Calculations of polar warming show that perihelion adiabatic heating can be highly variable from one Mars year to the next, and more than twice as strong as that for aphelion conditions (Bougher et al 2006b;Bell et al 2007). Finally, without the deep inter-hemispheric Hadley circulation made possible using these coupled lower and upper atmosphere simulations, winter polar warming features in the Mars thermosphere would not be reproduced at all (Bell et al 2007).…”
Section: Ncar Coupled Mgcm-mtgcm (Mars)mentioning
confidence: 98%
See 1 more Smart Citation
“…[17] The dust distribution in the lower atmosphere has been shown to have an important influence on the dynamics of the upper thermosphere [Bell et al, 2007]. For the simulation used in this study, we use a climatology of the dust as observed by the Thermal Emission Spectrometer on board the Mars Global Surveyor mission between 1999 and 2001, i.e., MY24-25.…”
Section: The Model Prediction Of No Emission and Comparison To Observmentioning
confidence: 99%
“…While dynamics in the upper atmosphere are thought to be driven primarily by solar EUV heating, studies have suggested that vertical dynamical coupling nevertheless plays an equally significant role on Mars as it does on Venus and Earth, most prominently in the form of strong wave signatures in the thermosphere that are not only formed in situ at those altitudes, but also include effects due to topography . Bougher et al (2006b) and Bell et al (2007) additionally proposed the existence of a deep inter-hemispheric circulation in order to enable thermospheric winter polar warming to operate. While most models available to-date still rely on implementing this coupling to lower altitudes as a lower boundary condition , codes are now appearing for Mars with a vertical range from the ground to the thermosphere (González-Galindo et al 2005), having the advantage of more self-consistently including processes of vertical dynamical coupling.…”
Section: Dynamics On Other Planets and Moonsmentioning
confidence: 98%